Seroprevalence of Bovine Viral Diarrhea Virus infection and associated risk factors in cattle in Selangor, Malaysia - Daves, Larry; Yimer, Nurhusien; Arshad, Siti Suri; Sarsaifi, Kazhal; Omar, Mohd Ariff; Yusoff, Rosnina; Haron, Abd Wahid; Abdullah, Faez Firdaus Jesse (Openventio Publishers, 2016)
Nurhusien Yimer/ Mohamed Ariff Omar,Jesse Faez Firdaus bin Abdullah,Rosnina Hj. Yusoff,Siti Suri Arshad,Abd Wahid Haron/ / , Kazhal Sarsaif,